2021
DOI: 10.1101/2021.04.13.439645
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Iron-sulfur clusters are involved in post-translational arginylation

Abstract: Eukaryotic arginylation is an essential post-translational modification that both modulates protein stability and regulates protein half-life through the N-degron pathway. Arginylation is catalyzed by a family of enzymes known as the arginyl-tRNA transferases (ATE1s), which are conserved across the eukaryotic domain. Despite its conservation and importance, little is known regarding the structure, mechanism, and regulation of ATE1s. In this work, we have discovered that ATE1s bind a previously unknown iron-sul… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 84 publications
0
12
0
Order By: Relevance
“…Based on our previous work, we have demonstrated that the [Fe-S] cluster-binding site is composed of Cys 23 and Cys 26 (part of a conserved CGYC motif) and Cys 94 /Cys 95 (part of a conserved CC motif). 32 While we have yet been able to crystallize the holo (cluster-replete) form of the protein, the AlphaFold model of ScATE1 supports co-localization of all four Cys residues in spatial proximity. Our apo structure reveals that the CGYC motif is part of a dynamic and disordered loop stretching from residues 15-33 (Supplementary Figure 7), and we speculate that this region becomes ordered in the presence of the [Fe-S] cluster.…”
Section: Overall Architecturementioning
confidence: 79%
See 4 more Smart Citations
“…Based on our previous work, we have demonstrated that the [Fe-S] cluster-binding site is composed of Cys 23 and Cys 26 (part of a conserved CGYC motif) and Cys 94 /Cys 95 (part of a conserved CC motif). 32 While we have yet been able to crystallize the holo (cluster-replete) form of the protein, the AlphaFold model of ScATE1 supports co-localization of all four Cys residues in spatial proximity. Our apo structure reveals that the CGYC motif is part of a dynamic and disordered loop stretching from residues 15-33 (Supplementary Figure 7), and we speculate that this region becomes ordered in the presence of the [Fe-S] cluster.…”
Section: Overall Architecturementioning
confidence: 79%
“…For example, our recent results have shown that ATE1 is multifaceted by also being an [Fe-S] cluster-binding enzyme. We posited that the presence of this cluster appears to function as an O 2 -dependent regulator to control post-translational arginylation in response to oxidative stress 32 , which is an important aspect of ATE1 function. While our new structure is apo (lacks the [Fe-S] cluster), it is tempting to speculate the mechanistic connection between cluster-binding in the N-terminal regulatory domain and alterations that could occur at the GNAT fold, and a metal-bound structure would significantly increase our understanding of this regulatory paradigm.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations